2023
DOI: 10.1097/j.jcrs.0000000000001113
|View full text |Cite
|
Sign up to set email alerts
|

Randomized and double-blind comparison of clinical visual outcomes of 2 EDOF intraocular lenses

Abstract: Symfony and Vivity EDOF IOLs provide similarly good visual outcomes. The Symfony group had increased reports of some visual disturbances, notably the frequency, severity, and bothersomeness of starbursts and glare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
(50 reference statements)
1
1
0
Order By: Relevance
“…Although EDOF lenses enable good vision without glasses for far and intermediate distances, some of the patients also gained functional near vision. Similar findings were also found in other studies 11,17,18 …”
Section: Discussionsupporting
confidence: 93%
“…Although EDOF lenses enable good vision without glasses for far and intermediate distances, some of the patients also gained functional near vision. Similar findings were also found in other studies 11,17,18 …”
Section: Discussionsupporting
confidence: 93%
“…Previous studies [ 2 , 22 , 24 , 25 , 26 ] have also demonstrated the effect of mini-monovision with a non-diffractive EDOF, Vivity IOL. While some recent studies have compared the bilateral implantation of the Vivity IOL with emmetropia and trifocal IOL, other types of EDOF IOL, or Monofocal IOL [ 12 , 27 , 28 , 29 , 30 , 31 , 32 ], our study compared the clinical outcomes of the Vivity IOL with mini-monovision trifocal and monofocal IOLs. This study showed that the bilateral implantation of a Vivity IOL with mini-monovision was beneficial for near- and intermediate-vision, with high patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%